Persepsi Mahasiswa Tentang Program Tahfidz Qur’an Sebagai Syarat Komprehensif dan Munaqasyah - Yuniar Handayani; Karliana Indrawari; Madi Apriadi (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2021)
The purpose of the study was to determine the development and implementation of the tahfidz program of at least 1 chapter with the tahfidz program of at least 1 juz as a condition for taking   the exam and to determine the supporting and inhibiting factors of students in participating in the tahfidz program of at least 1 juz. The type of research is field research. Primary data sources are data regarding student perceptions of the tahfidz program at least juz 'amma and secondary data sources in the form of documents, books, magazines, journals, and official websites. Data collection tools, namely observation, FGD, documentation, and in-depth interviews. The data were analyzed by data reduction, data processing, and data conclusions. The result of the research is that the tahfiz juz 30 program is very useful for students because in addition to being a prerequisite for thesis and munoqosah, the tahfiz juz 30 program also equips students in memorizing the Koran and providing religious knowledge as professional teachers in the future. Supporting factors for students to implement the tahfidz program are high student interest and motivation, the role of universities, family and student environmental conditions, facilities and infrastructure as well as community demands for the need to develop an Islamic spirit that will be carried out by professional teachers. While the inhibiting factor for students to take part in the tahfidz program is the lack of efficiency and time effectiveness.